2018
DOI: 10.1002/jcp.27547
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of noncoding RNAs in multiple myeloma: A review

Abstract: Multiple myeloma (MM) is a hematologic malignancy characterized by unrestricted secretion of monoclonal immunoglobulin and uncontrolled plasma cell proliferation. Extra‐medullary infiltration and drug resistance are two major obstacles in the treatment of MM. To solve these problems, it is necessary to elucidate the underlying pathological mechanisms and find new therapeutic targets. Noncoding RNAs (ncRNAs), which were once considered “transcriptional noise,” have been recognized as crucial regulators in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…Studies indicate that long non-coding RNAs (lncRNAs) play an important role in the pathophysiology of MM [54]. Recent studies have shown that prostate cancer-associated ncRNA transcript 1 (PCAT-1) plays an important role in the pathophysiology of MM and has a regulatory role in p38, where it induces an increase that correlates with proliferation and chemoresistance [55]. Therefore, regulating PCAT-1 could be an important therapeutic target in the context of regulating p38 in MM.…”
Section: Non-coding Rnas In the Regulation Of P38mentioning
confidence: 99%
“…Studies indicate that long non-coding RNAs (lncRNAs) play an important role in the pathophysiology of MM [54]. Recent studies have shown that prostate cancer-associated ncRNA transcript 1 (PCAT-1) plays an important role in the pathophysiology of MM and has a regulatory role in p38, where it induces an increase that correlates with proliferation and chemoresistance [55]. Therefore, regulating PCAT-1 could be an important therapeutic target in the context of regulating p38 in MM.…”
Section: Non-coding Rnas In the Regulation Of P38mentioning
confidence: 99%
“…Studies indicate that long non-coding RNAs (lncRNAs) play an important role in the pathophysiology of MM [53]. Recent studies have shown that prostate cancer-associated ncRNA transcript 1 (PCAT-1) plays an important role in the pathophysiology of MM and has a regulatory role in p38, where it induces an increase that correlates with proliferation and chemoresistance [54]. Therefore, regulating PCAT-1 could be an important therapeutic target in the context of regulating p38 in MM.…”
Section: P38 Regulation 221 Transcription Factors In the Regulation O...mentioning
confidence: 99%
“…130,131 Other Cancers Multiple myeloma (MM) is a malignant proliferative disease of plasma cells and is usually confined to the bone marrow. 132 Sun et al 133 found that the lncRNA MALAT1 is upregulated in MM and is negatively associated with miR-181a-5p. Moreover, this group demonstrated that in the context of MALAT1 interference, the proliferative and adhesive abilities of myeloma cells were inhibited, whereas apoptosis was promoted; miR-181a-5p overexpression exhibited similar effects on myeloma cells.…”
Section: Urogenital Cancersmentioning
confidence: 99%